Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem-Based Learning (PBL) di Kelas V Sekolah Dasar - Mardayani, Nadia; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
The research objective was to improve the learning outcomes of grade V students at SDN 01 Sungai Geringing, Padang Pariaman District. This research is a Classroom Action Research (CAR) using quantitative and qualitative techniques. Research procedures include planning, implementation, observation, and reflection. The data obtained in the study were processed using qualitative and quantitative data analysis models. A total of 29 people, including teachers and grade 5 students, became the research subjects. The results obtained: (1) The average value of lesson plans increased from 81.25% good (B) in cycle I to 95% very good (A) in cycle II. (2) From 76.78% good (B) in cycle I to 96.42% very good (A) in cycle II from the teacher's point of view. Even though the student dimensions increased, in cycle 1 he averaged 76.78% good (B), while in cycle 2 he was 96.42% very good (A). (3) Student learning outcomes in cycle I increased by 75.62% to Good (B) and in cycle II increased by 88.36% to Very Good (A). Thus, the PBL model can improve the learning outcomes of fifth-grade students at SDN 01 Sungai Geringing, Padang Pariaman Regency in integrated theme learning.